Defects of B-cell terminal differentiation in patients with type-1 Kabuki syndrome - Lindsley, Andrew W.; Saal, Howard M.; Burrow, Thomas A.; Hopkin, Robert J.; Shchelochkov, Oleg; Khandelwal, Pooja; Xie, Changchun; Bleesing, Jack; Filipovich, Lisa; Risma, Kimberly; Assa'ad, Amal H.; Roehrs, Phillip A.; et al. (Journal of allergy and clinical immunology, 2016)
Kabuki syndrome (KS) is a complex multisystem developmental disorder associated with mutation of genes encoding histone-modifying proteins. In addition to craniofacial, intellectual, and cardiac defects, KS is also characterized by humoral immune deficiency and autoimmune disease, yet no detailed molecular characterization of the KS-associated immune phenotype has been reported. We sought to characterize the humoral immune defects found in patients with KS with lysine methyltransferase 2D (KMT2D) mutations. We comprehensively characterized B-cell function in a cohort (n = 13) of patients with KS (age, 4 months to 27 years). Three quarters (77%) of the cohort had a detectable heterozygous KMT2D mutation (50% nonsense, 20% splice site, and 30% missense mutations), and 70% of the reported mutations are novel. Among the patients with KMT2D mutations (KMT2DMut/+), hypogammaglobulinemia was detected in all but 1 patient, with IgA deficiency affecting 90% of patients and a deficiency in at least 1 other isoform seen in 40% of patients. Numbers of total memory (CD27+) and class-switched memory B cells (IgM−) were significantly reduced in patients with KMT2DMut/+ mutations compared with numbers in control subjects (P < .001). Patients with KMT2DMut/+ mutations also had significantly reduced rates of somatic hypermutation in IgG (P = .003) but not IgA or IgM heavy chain sequences. Impaired terminal differentiation was noted in primary B cells from patients with KMT2DMut/+ mutations. Autoimmune pathology was observed in patients with missense mutations affecting the SET domain and its adjacent domains. In patients with KS, autosomal dominant KMT2D mutations are associated with dysregulation of terminal B-cell differentiation, leading to humoral immune deficiency and, in some cases, autoimmunity. All patients with KS should undergo serial clinical immune evaluations.